THE CHARACTERISTIC AND VARIABILITY OF SEA SURFACE TEMPERATURE IN JAVA SEA - Widada Sulistya; Agus Hartoko; S.Budi Prayitno (International Journal of Remote Sensing and Earth Sciences, 2007)
The phenomena of marine climate can be identified by the sea surface temperature, as Illahude (1999) reported that one of the parameters of oceanography which characterized of sea water mass is sea surface temperature (SST). The distribution of sea surface temperature can be used as an indicator of fishing ground. However, as understanding of marine climate variability it does not well enough (Hartoko,2000). The characteristic and variability of ST in Java Sea are not sufficiently enough understood. In order to better understand, we need the Spatial-Temporal Analysis of SST. The Spectral Analysis Method is used to study the characteristic and seasonal variation of SST, while GIS Analysis is used to study SST spatial distribution pattern. Temporally, the highest temperature at Java Sea occurs in April-May and November, whereas the lowest temperature in February and August. The SST fluctuation of Java Sea ranges from 27.48 degree of celcius to 29.66 degree of celcius and its periodic cycle generally occurs for 6 months, 1 year and 8 years.